Disintegrasi Ummat Islam Granada: Studi Kehancuran Pemerintahan Islam di Andalusia - Kurniawan, Taufiq; Hasanah AM, Azizah Uswatun (Al-Ijtima`i: International Journal of Government and Social Science, 2025)
Granada was the last Muslim territory in the Iberian Peninsula. The Islamic Kingdom of Granada was ruled by the descendants of the Banu Ahmar for two centuries and a half. During this period the leaders of the Banu Ahmar made Granada the center of the Islamic Kingdom in Andalusia and established the Al-Hamra Palace as the center of government. The Islamic Kingdom of Granada experienced various political turmoil caused by various internal and external factors which finally collapsed in 1492 AD. The end of the Islamic Kingdom of Granada also meant the end of the existence of Islam in the Iberian Peninsula.The peak of the decline of the Islamic Kingdom of Granada began when two large Christian kingdoms, namely the Kingdom of Castile and Aragon, united, and the Islamic Kingdom of Granada was led by weak leaders. Finally, Granada fell to the Christian kingdom in 1492 AD. The fate of the Muslim community in Granada ended in a very tragic story. Some of them were forced to convert to Christianity, others experienced very sad torture. The rest were forced to migrate to North African regions such as Morocco, Tunisia, and Algeria. Today, several historical Islamic buildings in Andalusia, such as palaces and mosques, still stand strong, but there are no descendants of the Muslim Andalusian community who are Muslims.